The Bromodomain testis-specific gene (Brdt) characterization and expression in gilthead seabream, Sparus aurata, and European seabass, Dicentrarchus labrax - M. Úbeda-Manzanaro; J.B. Ortiz-Delgado; C. Sarasquete (European Journal of Histochemistry, 2016)
Multiple genes and transcription factors are involved in regulation and control of the complex process of sex determination and differentiation of fish species. Also more, several hormonal factors and some environmental conditions can also be adequate spawning strategies and stimuli for inducing reproduction of fish species. Brdt gene belongs to the bromodomain-extraterminal domain (BET) family of transcriptional coregulators. In mammals, Brdt gene is almost exclusively expressed in testis. Furthermore, Brdt protein is involved in elongating spermatids, and is required for proper spermatogenesis and male fertility. However, from our understanding of fish species, the role of this gene as key, during gametogenesis, still remains unknown. In this study, two Brdt mRNA transcripts were isolated from two teleostean fish species, gilthead seabream and European seabass. In both species the shorter form lacked a functional C-terminal domain, which may involve a different function as transcriptional regulator. The pattern of Brdt expression showed that the highest levels occurred in the gonads. Significantly lower levels of expression were detected in brain, pituitary and different organ systems (heart, kidney, gills, among other somatic tissues) from both studied species. In situ hybridization approach evidenced that Brdt mRNA expression was restricted to specific cell-types of the germ line, during both oogenesis and spermatogenesis processes.